1-{2-[(2,4-Dichlorobenzylidene)amino]ethyl}-3-methylimidazolium hexafluorophosphate - Wen-Jie Zheng; Yi-Qun Li; Bin Li; Jie Liu (Acta Crystallographica Section E, 2009)
In the title Schiff base compound, C13H14Cl2N3+·PF6−, the dihedral angle between the aromatic ring and imidazole ring in the cation is 6.10 (2)°. Intermolecular C—H...F hydrogen-bonding interactions and π–π stacking interactions [centoid–centroid distance = 3.7203 (12) Å] help stabilize the crystal packing.